2022
DOI: 10.1002/rcm.9279
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical property evaluation of modified oligonucleotides by traveling‐wave ion mobility mass spectrometry

Abstract: Rationale Therapeutic oligonucleotides have molecular weights of more than 6000 Da. They typically contain chemically modified structures such as phosphorothioate (PS) and a locked nucleic acid (LNA). To determine the effect of the length and chemical modification on the physicochemical properties, various nucleic acids with different lengths and modified structures were analyzed using traveling‐wave ion mobility mass spectrometry (TWIMS). Methods The physicochemical characteristics of the modified oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…The mobiligram of the 8 mer PS-modified oligonucleotide is composed of 128 diastereomers, and the results show the sum of the separated peaks of these diastereomers. This broader mobiligram tendency has also been reported in previous studies. , …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The mobiligram of the 8 mer PS-modified oligonucleotide is composed of 128 diastereomers, and the results show the sum of the separated peaks of these diastereomers. This broader mobiligram tendency has also been reported in previous studies. , …”
Section: Resultssupporting
confidence: 90%
“…This broader mobiligram tendency has also been reported in previous studies. 25,26 siRNA Patisiran Impurity Isomer Separation by Cyclic IMS. Based on the above results, we selected the approved full-PO siRNA patisiran sense and antisense strands as models for oligonucleotide isomer separation to confirm the cyclic IMS separation capability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This transition is observed when around 50% of the molecule is charged, or in other words, when every other phosphate carries a negative charge. Those observations were also studied by Omuro et al 82 and more specifically the effect of the oligonucleotide sequence and length differences on the CCS values by traveling wave ion mobility spectrometry (TWIMS). They observed that when the charge states reached approximately one charge per 3.5–4 bases such as −4 to −5 charge states for 16‐mers, an inflection point was observed, which indicates that the oligonucleotides adopt two conformations in the gas phase, where the conformational change seems to occur around the inflection point.…”
Section: Application Of Ims To the Characterisation Of Oligonucleotidesmentioning
confidence: 94%
“…For example, in the current LC-UV/MS methodology, impurities with similar masses are simply reported as a single entity (e.g., n-U/n-C or n+U/n+C) with a sum quantity. Recent efforts have been directed toward both LC and MS dimensions to resolve isobaric/isomeric impurity ions. For example, ion pair-reversed phase (IPRP) LC has been fine-tuned to separate composite impurities and coupled with tandem mass spectrometry (MS/MS) to differentiate unresolved isomers in PO oligonucleotides. , Ion mobility MS has been employed to differentiate PS oligonucleotide diastereomers of short sequences , and to separate isomeric nucleotide residues following nucleic acid digestion. , Nevertheless, many challenges remain, particularly in the context of PS-modified ONTs.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 For example, ion pair-reversed phase (IPRP) LC has been fine-tuned to separate composite impurities and coupled with tandem mass spectrometry (MS/MS) to differentiate unresolved isomers in PO oligonucleotides. 10 , 15 Ion mobility MS has been employed to differentiate PS oligonucleotide diastereomers of short sequences 16 , 17 and to separate isomeric nucleotide residues following nucleic acid digestion. 11 , 18 Nevertheless, many challenges remain, particularly in the context of PS-modified ONTs.…”
Section: Introductionmentioning
confidence: 99%